Influência do espectro de gotas no desempenho de fungicidas na cultura do trigo - Gulart, Caroline Almeida (2013)
Leaf rust and leaf spots caused by Bipolaris sorokiniana and Drechslera tritici-repentis, are diseases that dramatically reduce the productivity of wheat. Depending on the difficulty in having cultivars resistant to all diseases, chemical control is an alternative, technically and economically viable. To maximize the residual of fungicides is necessary to optimize the factors related with spray minimizing the losses due to disease incidence. The goal of the work was to determine the influence of the number of drops in the penetration of fungicides and its control efficacy at various stages of application. The experimental design used was randomized block in Split plot design, totaling 20 treatments and four replications. The treatments were two wheat cultivars (Fundacep Cristallino and Fundacep Nova Era); three spray tips (XR 11002, TJ 60-11002 and TX 8002); 3 fungicides: Pyraclostrobin + Epoxiconazol; Epoxiconazol and Pyraclostrobin, and a control without any application. It was evaluated the density of drops per square centimeter, DMV, DMN, severity of disease, weight of hectoliter and productivity of the crop. The use of fungicides pyraclostrobin and epoxiconazol + piraclostrobia, respectively, provided the better control of diseases, higher productivity and greater weight of hectoliter in Nova Era cultivar. On the other hand, Cristalino cultivar with lower impact of the diseases did not show difference on efficacy of the fungicides used. The control of diseases was influenced by the DMV/DMN ratio due to the use of different spray tips. Tips with thin/medium drop spectrum performed better coverage at the lower part of the canopy, providing fewer establishments of the diseases. The correlation between the variables showed that the second application of fungicides was the one that crashed in the calculation of the area under the curve of progress of diseases (AACPD), hectoliter weight and yield. The greater disease pressure at flowering can explain this result.